Agriculture Three in One Mechanism - Rahul Mukund, Ingale; Ravi Ratan, Gomsale; Ravindra Dilip, Jadhav; Vaibhav Sunil, Jadhav; Patil, T. R. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The paper deals with utilization of alternative energy and it's converted into the energy, that's utilized to drive the assorted units of the system. Throughout this paper we tend to tend to had tried to elucidate but the assorted agriculture equipment’s unit combined and work in conjunction with potency with reducing the manufacturing value that is in a position to be in low-cost sire.
Keywords: cutting machine; spraying machine; dusting machine; agricultural vehicle